Source distance determination based on the spherical harmonics. (15th February 2017) - Koutny, Adam; Jiricek, Ondrej; Thomas, Jean-Hugh; Brothanek, Marek
Abstract: This paper deals with the processing of signals measured by a spherical microphone array, focusing on the utilization of near-field information of such an array. The processing, based on the spherical harmonics decomposition, is performed in order to investigate the radial-dependent spherical functions and extract their argument – distance to the source. Using the low-frequency approximation of these functions, the source distance is explicitly expressed. The source distance is also determined from the original equation (using no approximation) by comparing both sides of this equation. The applicability of both methods is first presented in the noise-less data simulation, then validated with data contaminated by the additive white noise of different signal-to-noise ratios. Finally, both methods are tested for real data measured by a rigid spherical microphone array of radius 0.15 m, consisting of 36 microphones for a point source represented by a small speaker. The possibility of determination of the source distance using low-order spherical harmonics is shown. Abstract : Highlights: Spherical harmonics based signal processing for spherical microphone array is summarized while focusing on the near field of such an array. Source distance determination with low-frequency approximation and without approximation is described. Presented methods are verified on the model simulation and real experimental data.